A produção e a comercialização do açaí-da-mata no município de Anori-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
In recent years, particularly since the 2000s, there has been a significant increase in demand for açaí and consequently its production. This increase was driven by the recognition of the product at both national and global levels, owing to its energy properties. According to data from the latest agricultural census conducted by the Brazilian Institute of Geography and Statistics (IBGE) in 2017, Amazonas is the second-largest producer of the fruit, trailing only the state of Pará. The municipality of Anori, the subject of this study, ranks as the fifth largest producer in the state, having produced 1,254 tons in 2017. However, according to the Sustainable Development Agency (ADS), with data from 2014, Anori is not among the Amazonian municipalities with agro-industries responsible for açaí production. This study aimed to investigate the mode of açaí production in the municipality of Anori, addressing not only production and the social organization of producers and processors but also the açaí commercialization network originating from the municipality. Additionally, it sought to understand the role of peasant labor in this context. To achieve these objectives, two field surveys were conducted in the study area. Açaí production in the municipality of Anori dates back many years, but initially, it was practiced manually to meet the dietary needs of the population. The main source of income for Anori residents was orange exports, which dominated the local economy for many years. However, changes in agricultural culture were driven by severe floods and pests affecting orange plantations, creating an opportunity for açaí, which was not previously seen as a significant source of income. Since then, açaí production in the municipality has gained recognition, especially in the city of Manaus, as one of the best açaí varieties in the state, due to its quality in both flavor and proper fruit handling. The research revealed that peasant activity is present at all stages, from planting to açaí processing, and that producers are not expropriated from the means of production. Currently, more than twenty açaí factories in the municipality, sending over 10,000 liters of açaí to Manaus daily during the harvest season, the primary destination for production. However, for this product to reach the main consumer market, an indispensable production chain involving various social actors is required, producers, gatherers, processors, transporters, and middlemen perform their roles with considerable difficulties and resistance to ensure their livelihoods
Keywords: .; .; .; CIENCIAS HUMANAS: GEOGRAFIA; Açaí-da-Mata; Anori; Camponês; Monopolização do território pelo capital